Atypical Radiographic Presentation of Cryptococcus Pneumonia in a Newly Diagnosed HIV Patient - Arthur Cacacho; Umair Ashraf; Arsalan Rehmani; Masooma Niazi; Misbahuddin Khaja (Case Reports in Infectious Diseases)
Background. Cryptococcus infection is an opportunistic infection that occurs primarily among immunocompromised patients, and the morbidity and mortality of this infection is high if left unrecognized and untreated. There are no clinical or radiographic characteristics typical of cryptococcal pneumonia, and its clinical and radiological presentations often overlap with other diagnoses. Case Presentation. We present a case of a 25-year-old man from Ghana admitted for an altered mental state, weight loss, neck pain, fever, and photophobia. He was diagnosed with Cryptococcus neoformans meningitis by cerebrospinal fluid culture and with disseminated cryptococcal infection by a positive Cryptococcus blood test. Diffuse micronodular opacities were found in a miliary pattern in the upper portions of both lungs upon imaging, which suggested miliary tuberculosis; thus, the patient was started on antituberculosis therapy. The patient underwent flexible fiber optic bronchoscopy, and transbronchial biopsy of the right lung showed bronchopneumonia with fungal spores consistent with filamentous Cryptococcus neoformans, which grew in tissue culture of the right lung. Interferon-gamma release assay, Mycobacterium tuberculosis PCR, and acid-fast bacilli staining of the bronchoalveolar lavage were negative for the M. tuberculosis complex. Conclusion. The similarities in clinical and imaging findings among patients with acute immunodeficiency syndrome with coinfections make diagnoses difficult; thus image-guided biopsies are essential to confirm diagnoses.